Educação e tecnologia: a visão do professor sobre a formação e atuação em cursos superiores de tecnologia - Neves Filho, Luiz Alberto (2022)
The present research discusses, based on empirical research, the perspectives of the model of Technological Education implemented throughout the historical process that circled the development of the university. Technological Education is studied based on the perception of teachers about their training and professional performance in the modality of higher technology courses. The theoretical and methodological reference adopted is linked to the theoretical contributions of the authors of the Critical Theory of Society, mainly Theodor Adorno, Herbert Marcuse, Walter Benjamin and Max Horkheimer. The objectives of the research are: a) analyze the political-economic structure that fostered the growth of technological education in Brazilian higher education; b) identify the impacts generated by technological education in the training process and in the teachers' field of action. The hypotheses raised at the beginning of the research were: a) technological education is linked to a political-economic-cultural structure that transformed the university into an administrative organization producing the commodity of labor force and reserve army for the industrial society; b) the process that generated the development of higher education - in the field of technological education - made teachers' training and their professional field of action limited and precarious. The research was carried out with professors who work in higher technology courses, and the questionnaire was sent to 200 professors from different public and private higher education institutions, according to the sampling plan. The results revealed that technological education has made teachers' training and working conditions limited and precarious. At the same time, the teachers presented, even though in a disjointed way, some tendencies of resistance and consternation to the process of precariousness of their training and of their professional field